Exercise for Athletes With Inflammatory Arthritis. Issue 9 (September 2018) - Powell, Amy P.; English, Joy
Abstract : Advances in pharmacologic management of inflammatory conditions have allowed those living with these conditions to pursue fitness activities previously difficult due to functional limitations. With that said, many patients with inflammatory arthritis are still not active enough. In this article, we review specific exercise recommendations for a number of inflammatory conditions with a focus on overall health promotion and cardiovascular disease risk reduction, discuss exercise as an adjunct to pharmacologic disease management, and review potential risks of sport participation for athletes with inflammatory arthritis conditions.